The effect of neuromuscular electrical stimulation on functional status and quality of life after knee arthroplasty: a randomized controlled study - Erbil, Elif; Paker, Nurdan; Bugdayci, Derya; Demircioglu, Demet Tekdos; Emre, Tuluhan Yunus (Journal of Physical Therapy Science, 2015)
[Purpose] The aim of this study was to investigate the effect of the addition of NMES to the post-TKA rehabilitation protocol on the functional status and quality of life of the patients. [Subjects and Methods] Patients were randomized into an exercise (control) and electrical stimulation (NMES) group. A home exercise program was prescribed for the control group. For the neuromuscular stimulation group 30 minute electrical stimulation applied to the vastus medialis muscle 5 days a week for 4 to 6 weeks. VAS, the timed up and go test, WOMAC and SF-36 scores were evaluated preoperatively and postoperatively at the first month and the third month of the follow-up period. [Results] Both the NMES group had 30 patients each, with 2 and 1 male patients respectively. The comparisons of WOMAC results at month 1 revealed that pain, stiffness, and total scores of the NMES group was significantly better than those of control group at the first and third months. Significantly better physical function and SF-36 subscales, except mental health, were found for the NMES group at the first month of follow-up. [Conclusion] The inclusion of the neuromuscular electrical stimulation program after knee arthroplasty was more effective at providing rapid improvements in knee pain, walking distance and quality of life.